Maturity status is correlated to basket performance of different competitive levels: Anthropometrical and physiological basis - Torres Unda, J.; Irazusta, A.; Gravina, L.; Zarrazquin, I.; Kortajarena, M.; Gil, J.; Irazusta, J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Anthropometrical and physiological features are undoubtedly important factors in determining success in basketball (Hoare, 2000; Torres-Unda et al., 2013). During the course of adolescent development, there are abrupt increases in size and weight, together with a rapid improvement of physical performance (Roemmich, & Rogol, 1995). However, the processes of maturation do not occur in everyone at the same age (Borsboon et al., 1996). The difference in maturation among adolescents may be very relevant because it can influence the functional capacity in basketball (Malina et al., 2004). Methods: We analyzed the relation of maturational status (measured as years from the age peak height velocity, APHV) of elite male basketball players (13-14 years old) and teams with anthropometrical and physiological parameters. We also analyzed points scored and performance index rating (PIR) in the Mini-cup tournament of the ACB. In addition, we calculated the differences in the years from APHV between different teams regarding their position in the tournament. Results: Boys who took part in this elite basketball tournament had an earlier maturation than their age-mates from the general population. Height, weight, arm span, hand length, femur length and sitting height of the players were strongly correlated (p<0.005) with the years from the APHV. However, sprint-time and jump capacity were not correlated with the above-mentioned parameters in the analyzed sample. Earlier maturation also correlated positively with PIR and points scored (p<0.05). Accordingly, the APHV (p <0.005) was highest among the finalist and semifinalist teams than for the rest of the teams. Discussion: Our results seem to demonstrate that during adolescence selection criteria for elite basketball teams are based on an early development. Early maturing players have transient anthropometrical advantages which can have a great effect in basketball performance (Delorme et al., 2011). In consequence, many talented latematuring players may be marginalized and their career stunted by a short-sighted method of selection.